Evaluation of Composting Methods for Organic Waste Reduction - Rahadi, Zulfikar; Manea, Elena Elisabeta; Rifai, Rıfat (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
The rapid increase in organic waste generation has become a critical environmental challenge, particularly in developing countries where landfill dependency remains high. Composting has been widely recognized as a sustainable and cost-effective method for reducing organic waste while producing value-added soil amendments. This study aims to evaluate and compare various composting methods in terms of their effectiveness in organic waste reduction, process efficiency, environmental performance, and socio-economic feasibility. A systematic literature-based evaluation was conducted using qualitative synthesis and comparative analysis of empirical findings from peer-reviewed international journals. The reviewed composting methods include windrow composting, aerobic composting, anaerobic composting, vermicomposting, in-vessel composting, pit composting, and hybrid systems. The results indicate that aerobic-based composting methods, particularly windrow and in-vessel systems, demonstrate higher waste reduction rates (40–95%), faster stabilization, and better compost quality compared to anaerobic and pit-based systems. Hybrid approaches combining windrow and vermicomposting were found to be effective in accelerating maturation and pathogen reduction. Furthermore, technological enhancements such as microbial inoculants and controlled aeration significantly improve composting efficiency. This study concludes that composting is a viable strategy for sustainable organic waste management, although method selection should consider local conditions, waste characteristics, and socio-economic factors. The findings provide valuable insights for policymakers and practitioners seeking to optimize composting systems for sustainable waste reduction.